The Maximal Wrinkle Angle During the Bubble Collapse and Its Application to the Bubble Electrospinning - He, Ji-Huan; Qian, Man-Yu; Li, Ya (Frontiers in Materials, 2022)
Polymer bubbles are ubiquitously used for the fabrication of nanofibers by the bubble electrospinning. When a bubble is broken, the fragments tend to be wrinkled. The wrinkle angle plays an important in controlling the fiber morphology during the bubble electrospinning. This paper shows the maximal angle is about 49°, which is close to the experimental value of 50°. This maximal angle can be used for the optimal design of the nozzle in the bubble electrospinning for the fabrication of non-smooth nanofibers.